Impacts of Constitutive and Induced Benzoxazinoids Levels on Wheat Resistance to the Grain Aphid (Sitobion avenae) - Zhanfeng Zhang (MDPI AG, 2021)
Benzoxazinoids are important secondary metabolites in gramineae plants and have inhibitory and toxic effects against a wide range of herbivore pests. However, the relationship between benzoxazinoid level and plant resistance to aphids remains controversial. In this study, we investigated the relationship between benzoxazinoids composition and concentration in wheat leaves and the resistance to the grain aphid Sitobion avenae. Overall, six benzoxazinoids were detected and identified by mass spectrometry based metabolites profiling, including three lactams, two hydroxamic acids, and one methyl derivative. The constitutive levels of these benzoxazinoids were significantly different among the wheat varieties/lines. However, none of these benzoxazinoids exhibited considerable correlation with aphid resistance. S. avenae feeding elevated the level of 2-O-β-D-glucopyranosyloxy-4,7-dimethoxy-(2H)-1,4-benzoxazin-3(4H)-one (HDMBOA-Glc) and reduced the level of 2-O-β-D-glucopyranosyloxy-4-hydroxy-7-(2H)-methoxy-1,4-benzoxazin-3(4H)-one (DIMBOA-Glc) in some of the wheat varieties/lines. Moreover, aphid-induced level of DIMBOA-Glc was positively related with callose deposition, which was closely associated with aphid resistance. Wheat leaves infiltrated with DIMBOA-Glc caused a noticeable increase of callose deposition and the effect was in a dose dependent manner. This study suggests that the constitutive level of benzoxazinoids has limited impact on S. avenae. Aphid feeding can affect the balance of benzoxazinoids metabolism and the dynamic level of benzoxazinoids can act as a signal of callose deposition for S. avenae resistance. This study will extend our understanding of aphid–wheat interaction and provides new insights in aphid-resistance wheat breeding.